2021
DOI: 10.5430/jnep.v12n1p25
|View full text |Cite
|
Sign up to set email alerts
|

How do practically trained (student) caregivers in nursing homes learn? A scoping review

Abstract: Background and objective: Practically trained (student) caregivers (further: caregivers) make up the majority of care staff in nursing homes (NHs). To keep up with the fast-changing healthcare environment and ensure a high quality of care, it is important to know how to stimulate continuous work-based learning (WBL) among this group. The purpose of the study was to systematically study the scientific literature published to date on (1) how caregivers learn in NHs and (2) what facilitates or impedes their learn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 65 publications
0
3
0
Order By: Relevance
“…In the case of NH care, the users of scientific knowledge are nursing and healthcare students and practitioners, and their teachers and educators. A recently published scoping review on the facilitators and barriers to learning among practice-trained students and practicing caregivers in NHs showed that they learn better when their learning needs are incorporated into educational programs, such as needs related to content, form, length, and use of language (Muller-Schoof et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…In the case of NH care, the users of scientific knowledge are nursing and healthcare students and practitioners, and their teachers and educators. A recently published scoping review on the facilitators and barriers to learning among practice-trained students and practicing caregivers in NHs showed that they learn better when their learning needs are incorporated into educational programs, such as needs related to content, form, length, and use of language (Muller-Schoof et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…[22][23][24][25] As a result, the PCPI-S has not been tested and/or validated by this majority in an NH setting at the moment of publication of this study. From an earlier study, [29] we know that learning materials for practically trained caregivers should not be too long, should not contain difficult vocabulary, and should not be incomprehensible. Our PCC self-scan has taken this into account.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, Aase (26) reports that NH managers tend to underestimate their influence on the CLE. To our knowledge, research on apprentices' learning is scarce: a recent review (27) identified no studies focusing how nursing apprentices and assistants learn in NHs.…”
Section: Basic Nursing and Placement Learningmentioning
confidence: 99%